A velhice e o consumo de marcas: um estudo exploratório sobre a percepção do envelhecimento e o consumo de marcas - Garcia, Tatiana Cruz (2018)
This study aims to investigate how public perception between 60 and 75 years on the old age can impact the consumption and the profile of the marks non-durable consumer goods, including goods openly addressed to this age group. The topics covered in the theoretical review are related to old age, aging, losses and gains in this process, construction of the identity of the old, denial of old age, the role of media in process and active aging. For the development of the researches, a qualitative method was used with in-depth exploratory interviews with people between the ages of 60 and 75, residents of the city of São Paulo, class AB and independent from the point of view of mobility. The interviews were divided into five major blocks: (1) perception on aging, old age and its impact on relations with society, family and in the personal sphere; (2) perception about the terms used by society to describe people over 60; (3) relationship with brands in general; (4) relationship with brands openly targeted at people over 60; (5) projection of old age. At the end of the study it was possible to map a great opportunity in the development of products, especially in the food segment, which the specific functional needs of the elderly, such as food with low sodium content, more calcium, no lactose, more collagen and so on. But the hypothesis, which can be further explored in future studies, is that this opportunity should be approached, apparently, in a subtle and almost silent way. The communication should be conducted with the aim of ensuring the impact of the target audience by means of a channel segmentation strategy, without giving much prominence to generational issues in the message, avoiding the citation of terms and signs that age.